Aboriginal Studies Years 7-10 Syllabus (Board of Studies NSW, 2003)
Aboriginal Studies provides students with opportunities to develop knowledge and understanding of the diverse cultures, identities and lived experiences of Aboriginal Peoples. It explores the fundamental significance of land and spirituality, the importance of autonomy and self-determination, and contemporary issues affecting local Aboriginal communities and communities across Australia. Students have opportunities to develop research and consultation skills to engage respectfully with Aboriginal communities, and become active and informed advocates for a just and inclusive world. Aboriginal Studies is designed to be inclusive of all students in NSW schools, and is of value to Aboriginal and/or Torres Strait Islander students and non-Aboriginal students. The Aboriginal Studies Years 7–10 course includes Life Skills outcomes and content for students with disability.